Time-Splitting Coupling of WaveDyn with OpenFOAM by Fidelity Limit Identified from a WEC in Extreme Waves - Pierre-Henri Musiedlak (Energies, 2020)
Survivability assessment is the complexity compromising Wave energy development. The present study develops a hybrid model aiming to reduce computational power while maintaining accuracy for survivability assessment of a Point-Absorber (PA) Wave Energy Converter (WEC) in extreme Wave Structure Interaction (WSI). This method couples the fast inviscid linear potential flow time-domain model WaveDyn (1.2, DNV-GL, Bristol, UK) with the fully nonlinear viscous Navier–Stokes Computational Fluid Dynamics (CFD) code OpenFOAM (4.2, OpenFOAM.org, London, UK). The coupling technique enables the simulation to change between codes, depending on an indicator relating to wave steepness identified as a function of the confidence in the linear model solution. During the CFD part of the simulation, the OpenFOAM solution is returned to WaveDyn via an additional load term, thus including viscous effects. Developments ensure a satisfactory initialisation of CFD simulation to be achieved from a `hot-start’ time, where the wave-field is developed and the device is in motion. The coupled model successfully overcomes identified inaccuracies in the WaveDyn code due to the inviscid assumption and the high computational cost of the OpenFOAM code. Experimental data of a PA response under extreme deterministic events (NewWave) are used to assess WaveDyn’s validity limit as a function of wave steepness, in order to validate CFD code and develop the coupling. The hybrid code demonstrates the applicability of WaveDyn validity limit and shows promising results for long irregular sea-state applications.